Computational, dielectric and electro-optical analysis of an orthoconic antiferroelectric mesogen having superstructure in its reduced symmetry phase. Issue 1 (17th February 2021) - Gupta, Deepak; Kula, Przemyslaw; Bhattacharjee, Ayon
Abstract: The study presents a comprehensive analysis of a novel octan-2-yl 4'-(4-4-[3-(butanoyloxy)propoxy]benzoyloxybenzoyloxy)-[1, 1'-biphenyl]-4-carboxylate ( abb. as OAFLC-108), an orthoconic antiferroelectric liquid crystal. Its paramorphic sequence is estimated from defect studies. Its optimised structure, interatomic charge distribution and dynamics, global parameters and nonlinear optical properties are calculated by density functional theory. Vibrational modes are determined experimentally and theoretically. Low-frequency dielectric spectra are studied in view of molecular fluctuations, activation energy and relaxation time. The moderate value (29.5 nC/cm 2 ) of spontaneous polarisation and a response time of 2 ms support the candidature of OAFLC-108 as a competitive optoelectronic material.